The Role of Mayors and Barangay Captains in the Philippines' Anti-Drugs Campaign - Mendoza, Ronald U (Archīum Ateneo, 2018)
This research attempts to examine the legal mandate of Philippine local government officials, mayors and barangay captains, within the national government’s anti-illegal drug campaign, notably the police-led Project Double Barrel and Oplan Tokhang. To determine their duties, the General Welfare Clause from the Local Government Code of 1991 and the issuances from the Department of the Interior and Local Government on organizing Anti-Drug Abuse Councils (ADACs) in the barangay level are examined, among others. A geographical mapping of the drug-related killings in the barangay and district levels of Quezon City and City of Manila potentially illustrates the extent that the local officials may have perpetrated – or resisted – the punitive approach of the police. The research offers a counter-narrative, asking pointed questions on whether and to what extent the local officials, in reality, committed gross negligence and dereliction of duty by allowing a high death toll in their jurisdictions; thus threatening the security, safety, and human rights of their constituents.